Elastase in the pathogenic free-living amoebae Naegleria and Acanthamoeba spp. - Ferrante, A (1988)
The data showed that pathogenic free-living amoebae contain the proteolytic enzyme elastase. The levels of enzyme were similar in Naegleria fowleri, N. australianis italica, and Acanthamoeba culbertsoni A-1. No difference was found between elastase levels in a highly pathogenic N. fowleri and those in the same organism which had lost pathogenicity as a result of long-term axenic maintenance.